Prevalence and Determinants of Smokeless Tobacco Use Among Women in Urban Slums of Vidarbha, Maharashtra, India - Guntiwar, Manasi; Saoji, Ajeet; Khurana, Kartik; Saoji, Prachi (National Journal of Community Medicine, 2026)
Background: Smokeless tobacco (SLT) use remains a major public health concern in India, particularly among women living in urban slum settings. Evidence on its prevalence and determinants in this population remains limited. Methods: A community-based cross-sectional study was conducted among 300 women residing in urban slums of Vidarbha. Data on socio-demographic characteristics, SLT use, and behavioral factors were collected through face-to-face interviews. Statistics summarized participant characteristics and prevalence. Bivariate analysis using the Chi-square test estimated associations, while multivariate logistic regression was used to identify independent determinants. Results: The prevalence of SLT use was 21.3%. In bivariate analysis, SLT use was associated with older age, low educational attainment, employment status, and family tobacco exposure. In the adjusted model, low educational attainment (AOR = 8.61; 95% CI: 4.17-19.2) and employment status (AOR = 2.64; 95% CI: 1.42-5.01) emerged as independent determinants. Khara was the most commonly consumed product. Peer pressure, indigestion-related reasons, and thrill-seeking behavior were the most frequently reported reasons for initiation. Conclusion: SLT use is highly prevalent among women in urban slums, driven primarily by educational and occupational factors. Targeted, community-based interventions focusing on literacy and socio-behavioral change are essential to reduce SLT use and associated health risks.